2017
DOI: 10.1007/s12402-016-0214-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of circadian function, chronotype and chronotherapy in attention deficit hyperactivity disorder

Abstract: Reports of sleep disturbances in attention deficit hyperactivity disorder (ADHD) are common in both children and adults; however, the aetiology of such disturbances is poorly understood. One potentially important mechanism which may be implicated in disrupted sleep in ADHD is the circadian clock, a known key regulator of the sleep/wake cycle. In this systematic review, we analyse the evidence for circadian rhythm changes associated with ADHD, as well as assessing evidence for therapeutic approaches involving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 104 publications
(96 reference statements)
7
134
0
1
Order By: Relevance
“…Eveningness and sleep problems are common in adults with ADHD 31 . However, the actigraphy data showed that in the current study the participants of the ADHD and the Cont groups had, overall, similar sleep profiles in the post-training night, except for the tendency of the ADHD participants to have longer sleep latency periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eveningness and sleep problems are common in adults with ADHD 31 . However, the actigraphy data showed that in the current study the participants of the ADHD and the Cont groups had, overall, similar sleep profiles in the post-training night, except for the tendency of the ADHD participants to have longer sleep latency periods.…”
Section: Discussionmentioning
confidence: 99%
“…This is an increasingly common finding in young adults and adolescents, attributed to the use of light-emitting devices at evening hours 54 . We also tested for a possible relationship between the participants’ chronotype and their learning abilities, given that training and testing took place in the morning hours 31 . Evening oriented participants are more likely to show lower arousal levels and lower cognitive performance 55 during the morning hours compared to morning-oriented peers, and we conjectured that this may lead to a less engaging learning experience and subsequently to the expression of smaller delayed gains in performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a mechanistic perspective, a number of cellular and molecular processes have been identified to interact with the clock and modulate mood, including hypothalamic-pituitary-adrenal axis function, immune and neuroimmune processes, neurogenesis and direct control of neurotransmitter and neuromodulator systems 62. Circadian changes have also been described in a number of other psychiatric conditions, including schizophrenia,63 attention deficit hyperactivity disorder,64 obsessive compulsive disorder65 and borderline personality disorder 66. As such, circadian processes appear to be important transdiagnostic factors to consider in psychiatry and clinical psychology.…”
Section: Circadian Rhythms and Healthmentioning
confidence: 99%
“…eveningness) and disturbances (e.g. sleep problems) have been repeatedly associated with ADHD and/or ADHD symptoms [25]. These problems have also been linked to BMI variation and obesity.…”
Section: Introductionmentioning
confidence: 99%